The association between experiencing discrimination and physical and mental health among PWID - Couto e Cruz, C.; Salom, C.; Dietze, P.; Burns, L.; Alati, Rosa (Elsevier BV, 2019)
Background: Discrimination can be a daily issue in the lives of people who inject drugs (PWID). However, the extent to which discrimination is related to the health of PWID remains unclear. Methods: Data focusing on discrimination against PWID and potential health correlates were collected as part of the 2013 Illicit Drug Reporting System, a national survey with 887 PWID recruited in all Australian states and territories. Experience of discrimination, its setting, perceived reason and outcome, were self-reported by participants. The Kessler-10 scale and the mental component score of the Short Form 12-Item Health Survey were used to measure mental health. Physical health was assessed using the physical component score of the Short Form 12-Item Health Survey, specifically questions assessing injecting related problems and risk behaviour. Poisson and multinomial regression analyses were performed. Models were adjusted for socio-demographic and drug-related covariates. Findings: PWID reported experiencing discrimination in pharmacies, hospitals, government services and doctors/prescribers. The most commonly reported instances of discrimination were being refused service and experiencing abuse and/or violence. Experience of discrimination was associated with mental and physical health indicators. PWID who experienced discrimination were more likely to report high or very high mental distress (ARRR = 2.4, CI95 = 1.5–3.6) and mental health problems (ARRR = 1.4, CI95 = 1.2–1.7). The mental functioning (ARRR = 1.3, CI95 = 1.1–1.4) and physical functioning (ARRR = 1.1, CI95 = 1.1–1.4) of PWID, who experienced discrimination, were also more likely to be below Australian population mean scores. Conclusion: Self-reported experience of discrimination was associated with poor mental and physical health amongst PWID.